The Effect of Income and Impulsive Buying on Gen Z Investment Decisions in Kediri City with Self Control as a Moderating Variable - Hasanah, RA. Nurul; Harianto, Kukuh; Sutapa, Heru (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine and analyze the effect of income and impulsive buying on gen Z investment decisions in Kediri City with self control as a moderating variable. The data taken for this study is the response from participation, the response is taken using a questionnaire method with purposive sampling technique. In this study, the population is gen Z with the characteristics of the people of Kediri City and already has an income registered with the Badan Pusat Statistik (BPS) of Kediri City. The data collection method is a questionnaire and the data analysis method is a Structural Equation Model (SEM) based on Partial Least Square (PLS) assisted by SmartPLS software. The results showed that: 1) There is no significant influence between income on investment decisions. 2) There is a significant influence between impulsive buying on investment decisions. 3) There is a significant influence between income on investment decisions with self control as a moderating variable 4) There is no significant influence between impulsive buying on investment decisions with self-control as a moderating variable.